Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
h(x) + g(x) = f(x)
=> h(x)= f(x) - g(x) = \(3x^4+2x^2-2x^4+x^2-5x-\left(x^4-x^2-2x+6+3x^2\right)=x^2-3x-6\)\(h\left(-\dfrac{1}{3}\right)=\left(-\dfrac{1}{3}\right)^2-3\left(-\dfrac{1}{3}\right)-6=\dfrac{-44}{9}\)
\(h\left(\dfrac{3}{2}\right)=\left(\dfrac{3}{2}\right)^2-3\cdot\dfrac{3}{2}-6=-\dfrac{33}{4}\)
\(x^2-3x-6=0\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3+\sqrt{33}}{6}\\x=\dfrac{3-\sqrt{33}}{6}\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
:))
Ta có:
h(x)= -2x2 - 3x3 - 5x + 5x3 - x + x2 + 4x + 3 + 4x2-( 2x2 - x3 + 3x + 3x3 + x2 - x - 9x + 2)
=> h(x)=-2x2 - 3x3 - 5x + 5x3 - x + x2 + 4x + 3 + 4x2-2x2 + x3 - 3x - 3x3 - x2 + x + 9x - 2)
=> h(x)=x2+5x-2
b,
Cho x2+5x-2=0
=> ... tự giải :))
a,f(x)=2x^3+3x^2-2x+3
g(x)=2x^3+3x^2-7x+2
h(x)=f(x)-g(x)=(2x^3+3x^2-2x+3)-(2x^3+3x^2-7x+2)
=2x^3+3x^2-2x+3-2x^3-3x^2+7x-2
=(2x^3-2x^3)+(3x^2-3x^2)+(-2x+7x)+(3-2)
=5x+1
b,Đặt_h(x)=5x+1=0
5x=0-1
5x=-1
x=-1/5
Vậy_nghiệm_của_đa_thức_h(x)_là_-1/5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(f\left(x\right)+h\left(x\right)-g\left(x\right)\)
\(=\left(5x^4+3x^2+x-1\right)+\left(-x^4+3x^3-2x^2-x+2\right)\)
\(-\left(2x^4-x^3+x^2+2x+1\right)\)
\(=\left(5x^4-x^4-2x^4\right)+\left(3x^3+x^3\right)+\left(3x^2-2x^2-x^2\right)\)
\(+\left(x-x-2x\right)+\left(-1+2-1\right)\)
\(=2x^4+4x^3-2x\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a)
$f(x)=3x^3+4x^2-2x-1-2x^3=(3x^3-2x^3)+4x^2-2x-1=x^3+4x^2-2x-1$
b)
$h(x)=f(x)-g(x)=(x^3+4x^2-2x-1)-(x^3+4x^2+3x-2)$
$=(x^3-x^3)+(4x^2-4x^2)-(2x+3x)-1+2=1-5x$
c)
$h(x)=0\Leftrightarrow 1-5x=0\Leftrightarrow x=\frac{1}{5}$
Vậy $x=\frac{1}{5}$ là nghiệm của $h(x)$
![](https://rs.olm.vn/images/avt/0.png?1311)
f(x) +g(x) + h(x)
=(2x4 - x3 + x - 3 + 5x5) + (-x5 + 5x2 +4x + 2 + 3x5) + (x2 + x + 1 + 2x3 + 3x4)
= 2x4 - x3 + x - 3 + 5x5 +(-x5) + 5x2 +4x + 2 + 3x5 + x2 + x + 1 + 2x3 + 3x4
= 7x5 + 5x4 + x3 +x2 + 6x
f(x) - g(x) - h(x)
=(2x4 - x3 + x - 3 + 5x5) - (-x5 + 5x2 +4x + 2 + 3x5) - (x2 + x + 1 + 2x3 + 3x4)
=2x4 - x3 + x - 3 + 5x5 +x5 - 5x2 -4x - 2 -3x5 - x2 - x - 1 - 2x3 - 3x4
= 3x5 - x4 - 3x3 - 6x2 - 4x - 6